Pengaruh Faktor-faktor Manajerial terhadap Budaya Organisasi serta Implikasinya pada Kinerja Manajerial - Syaifuddin, S (Jurnal Trikonomika, 2012)
This research is conducted by applying descriptive and verifying method. Sampling technique used is proportional random sampling with number of sample is 221 samples. The analysis tool utilized is path analysis. The result of this research shows that: 1) the condition and implementation of Human Resources Management (HRM) Strategies, implementation of organization culture as well as managerial performances at PTPN IV and PTPN III are categorized good; 2) the correlation among independent variables are moderate. The lowest result of this correlation is 0.432 for variable X2 and X3, while the strongest correlation is 0.513 for variable X1 and X3; 3) there is significant influence of all independent variables on organization culture at PTPN IV and PTPN III that is 79.423%; 4) there is significant influence of organization culture variables on managerial performances at PTPN IV and PTPN III North Sumatera that is 87.70%.